EFFECTIVENESS AND SUPERVISION OF PARTICIPATING INTEREST BY THE BPMA: A LEGAL ANALYSIS - Wahyudi Wahyudi (Kanun Jurnal Ilmu Hukum, 2022)
Participating Interest policy (PI) is a new policy in oil and gas working areas; however, the implementation is not optimal. So there needs to be a study on effectiveness and supervision. This paper aims to discuss the formulation of the problem of the effectiveness of the implementation of PI and supervision by the Aceh Oil and Gas Management Agency (BPMA). This is a pure legal research meaning that it only requires data from relevant laws and analyses them  descriptively. The Regulation of the Minister of Energy and Mineral Resources Number 37 of 2016 concerning Provisions for Offering 10% of PI in Oil and Gas Working Areas is an implementing regulation. In addition, the Contractors’ Cooperation Contract is required to offer PI to regions. However, there is no  sanction for ignoring it which causes ineffectiveness. The Supreme Audit Agency reveals that Aceh had not yet received PIs from several working areas although the BPMA is entitled to do supervision.